2009
DOI: 10.1038/nn.2344
|View full text |Cite
|
Sign up to set email alerts
|

Awake replay of remote experiences in the hippocampus

Abstract: Hippocampal replay is thought to be essential for the consolidation of event memories in hippocampal–neocortical networks. Replay is present during both sleep and waking behavior, but while sleep replay involves the reactivation of stored representations in the absence of specific sensory inputs, awake replay is thought to depend on sensory input from the current environment. Here we show that stored representations are reactivated during both waking and sleep replay. We found frequent awake replay of sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

61
847
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(913 citation statements)
references
References 37 publications
61
847
4
1
Order By: Relevance
“…This view may be supported by studies which have indicated that patterned replay can occur for hours (e.g. Karlsson & Frank, 2009) and up to a day (Kudirmoti et al, 1999) after training. If a short period of recurrent activation is necessary to consolidate an extra-hippocampal trace for some tasks, this is consistent with the observation that span of temporally graded amnesia in flavor/odor cued conditioning is 1-2 days (Clark et al, 2002;Tse et al, 2007;Winocur et al, 2001;Winocur, 1990).…”
Section: Histologymentioning
confidence: 88%
“…This view may be supported by studies which have indicated that patterned replay can occur for hours (e.g. Karlsson & Frank, 2009) and up to a day (Kudirmoti et al, 1999) after training. If a short period of recurrent activation is necessary to consolidate an extra-hippocampal trace for some tasks, this is consistent with the observation that span of temporally graded amnesia in flavor/odor cued conditioning is 1-2 days (Clark et al, 2002;Tse et al, 2007;Winocur et al, 2001;Winocur, 1990).…”
Section: Histologymentioning
confidence: 88%
“…Studies in human subjects show that overlapping hippocampal networks are activated during episodic recall and imagination of fictitious experiences (Hassabis et al 2007). In animals, sharp-wave ripples can activate cells along both past and future trajectories (Karlsson and Frank 2009;Gupta et al 2010;Pfeiffer and Foster 2013). Pfeiffer and Foster (2013), for example, trained rats to find a rewarded well within a large environment while sharp-wave ripple-associated replay events were recorded in the hippocampus.…”
Section: Memory Consolidation and Retrievalmentioning
confidence: 99%
“…When we discuss the duration of a memory trace, we mean that this trace is maintained (e.g. by spontaneous replay during sleep (Wilson & Mcnaughton 1994) or waking (Karlsson & Frank 2009) or other mechanisms) without retrieving the cache and either leaving the item in place or rehoarding it (Grubb & Pravosudov 1994). Maintenance could happen by travelling through the area where caches are located, and then triggering the memories for the cache locations, which are thereby reconsolidated (Nader et al 2000a,b).…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%